Sulphur isotopes in deep groundwater reservoirs: Evidence from post-stimulation flowback at the Pohang geothermal facility, Korea. (March 2021) - Banks, David; Boyce, Adrian J.; Westaway, Rob; Burnside, Neil M.
Highlights: The 4.2 km deep Pohang PX-1 well was subject to hydraulic stimulation. Sulphate concentration and δ 34 S increase during post-stimulation flowback. Excess SO4 2− demonstrates mineral dissolution during hydraulic stimulation. Isotopes and modelling indicate anhydrite dissolution as probable sulphate source. Abstract: A hydraulic stimulation was carried out on a granodiorite reservoir in an enhanced geothermal system in August 2017 in Pohang, Korea. Water injected into the 4.2 km deep PX-1 well contained c. 330−360 mg/L sulphate, with a negative δ 34 S. The resulting flowback water became more saline with time, with sulphate and chloride concentrations and dissolved sulphate δ 34 S all increasing. Compared with conservative advective-dispersive and mixing models, the flowback contained surplus sulphate with an elevated δ 34 S. The PX-1 reservoir fluid is saturated with respect to anhydrite at downhole temperatures and pressures. Dissolution by injected surface water of secondary anhydrite along fracture surfaces, most likely with elevated δ 34 S reflecting the reservoir fluid, is likely to have resulted in an excess of 34 S-enriched sulphate in the flowback fluid. An alternative hypothesis involving oxidation of pyrite is also plausible but is stoichiometrically inadequate to account for the observed sulphate excess, and unlikely from a sulphur isotopic perspective. This analysis thus contributes to the evidence for water-rock reactions during stimulation of the Pohang granodiorite.